Psychometric properties of the Thai Internalised Stigma Scale (TIS-LCH) for care home residents - Tosangwarn, Suhathai; Clissett, Philip; Blake, Holly (Taylor & Francis, 2017)
Objectives: Living in a care home is a source of stigma in Thai culture, although there is currently no measurement tool in the Thai language specifically designed to assess internalised stigma in care home residents. The Thai Version of Internalised Stigma of Living in a Care Home (TIS-LCH) scale was developed and tested for its psychometric properties among Thai older residents. Methods: The Thai version of Internalised Stigma of Mental Health Illness (ISMI) Scale was revised into the TIS-LCH by replacing the word of “mental health illness” to “living in a care home”. Content validity of the TIS-LCH was determined through expert review (n=6), and reliability testing was undertaken with older care home residents (n=128). Results: The TIS-LCH showed good internal consistency, with a Cronbach’s alpha of 0.87. Test-retest reliability coefficient of TIS-LCH was excellent for the full scale (ICC=.90). Conclusions: The Thai version of IS-LCH (TIS-LCH) is a valid and reliable measurement tool for assessing internalised stigma in Thai care home residents. Clinical Implications: The IS-LCH will be a useful research tool to assess internalised stigma in older adults living in care settings. Understanding stigma will help health and social care professionals to plan interventions aimed at reducing or preventing negative emotional reactions and negative behavioural responses toward stigma, which are known to be associated with mental illness and particularly depression among this population.